THE INFLUENCE OF UPCOMMING TRANSPORT CONSTRUCTIONS ON THE TRAFFIC SITUATION IN THE CITY DISTRICT OF PRAGUE 6 (Perner's Contacts, 2014)
The paper describes the influences of three significant transport constructions – the Blanka tunnel complex, the extension of the subway route V.A, and the modernized railway track No. 120 with the turn-off to airport Ruzyně; on the traffic situation in the city district of Prague 6. The assessment of these influences was performed in the Traffic concept created on CTU FTS.
Keywords: Prague 6; the Blanka tunnel; subway; railroad to airport; influence